River, Coastal and Estuarine Morphodynamics 2006
DOI: 10.1201/9781439833896.ch11
|View full text |Cite
|
Sign up to set email alerts
|

Sediment patches, sediment supply, and channel morphology

Abstract: Bed surface particle size patchiness may play a central role in bedload and morphologic response to changes in sediment supply in gravel-bed rivers. Here we test a 1-D model (from Parker ebook) of bedload transport, surface grain size, and channel profile with two previously published flume studies that documented bed surface response, and specifically patch development, to reduced sediment supply. The model over predicts slope changes and under predicts average bed surface grain size changes because it does n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The higher τc50* on the G patches compared to the gC and cG patches (Figure 4a,b) was an unexpected result given that previous studies have documented that finer patches are either more mobile than, or are equally mobile as, coarse patches (e.g., Dietrich et al, 2005; Hodge et al, 2013; Lisle, 1995; Scheingross et al, 2013; Vericat et al, 2008; Yager et al, 2012a). In addition, τc50* (~0.4) for the G patches was larger than the normally reported range of values even in steep channels (e.g., Lamb et al, 2008).…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…The higher τc50* on the G patches compared to the gC and cG patches (Figure 4a,b) was an unexpected result given that previous studies have documented that finer patches are either more mobile than, or are equally mobile as, coarse patches (e.g., Dietrich et al, 2005; Hodge et al, 2013; Lisle, 1995; Scheingross et al, 2013; Vericat et al, 2008; Yager et al, 2012a). In addition, τc50* (~0.4) for the G patches was larger than the normally reported range of values even in steep channels (e.g., Lamb et al, 2008).…”
Section: Resultsmentioning
confidence: 70%
“…For example, small grains on fine patches could have high protrusions, whereas on coarse patches, small grains may have low protrusions and be more difficult to move. However, in other studies, a given grain size moved at the same flow magnitude for all underlying patch GSD (Dietrich et al, 2005; Yager et al, 2012b), suggesting that local protrusion and flow hydraulics do not affect sediment motion. For example, coarser patches could systematically be subjected to higher near‐bed stresses than fine patches thereby possibly increasing local grain mobility (Monsalve et al, 2016).…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…In fact, during floods both coarse material and fine fractions (sand) could be transported and the interactions between the coarse and the fine fractions could affect the bed-load transport and the associated migrating behavior. According to previous literature works [57][58][59][60], the coarse particles slow or stop each other, but the presence of finer particles trapped in their interstices determines that their mobility becomes higher. Braudrick et al [61], as an example, indicated that the fine sediments represent a critical element to maintain the rapid bar growth rate and sediment transport controlling the braided rivers.…”
Section: Discussionmentioning
confidence: 97%
“…Gravel-bed rivers respond to reductions in sediment supply not only through vertical sorting (armoring), but also through the development and expansion of coarse fixed patches (Nelson et al, 2009;Yager et al, 2015). Differences in grain-size distribution between the wetted channel and the bars can be considered as a measure of these crosssectional sorting patterns and a proxy for bed patchiness (Singer, 2008), and can be related to sediment supply conditions (Dietrich et al, 2005;Nelson et al, 2009Nelson et al, , 2010. Related to this, bars can be regarded as either the result of self-organization of more mobile sediments rapidly transiting along the riverbed (capacity-limited conditions; Church and Jones, 1982), or as relict features resulting from the concentration of bedload into a narrow band of the channel following sediment supply reductions leading to thalweg incision and lateral disconnection of the elevated bars (supply-limited conditions; Singer, 2008).…”
Section: Grain-size Distribution As a Metric Of Channel Adjustment To...mentioning
confidence: 99%